Recombinant vaccine protects juvenile hybrid grouper, Epinephelus fuscoguttatus × Epinephelus lanceolatus, against infection by Vibrio alginolyticus - Rosli, Nehlah; Nawi, Mohd Firdaus; Nik Yusoff, Nik Haiha; Abd Karim, Murni Marlina; Saad, Mohd Zamri; Md Yasin, Ina Salwany (Springer, 2017)
Vibrio alginolyticus has been recognized as one of the most significant bacterial diseases in grouper species. In this study, two outer membrane proteins of V. alginolyticus, the OmpK and OmpW, were considered for vaccine development, since both OmpK and OmpW were proven by previous studies to be promising vaccine candidates. Recombinant vaccines were constructed by cloning the OmpK and OmpW genes of V. alginolyticus into pET32 Ek/LIC vector and expressed in Escherichia coli. Fish were immunized with inactivated E. coli expressing the OMPs. Juvenile hybrid groupers, Epinephelus fuscoguttatus × Epinephelus lanceolatus, were divided into five groups of 150 fish per group. Group 1 was vaccinated IP with rOmpK while group 2 with rOmpW; group 3 was vaccinated with host E. coli BL21(DE3), group 4 with phosphate-buffered saline (PBS) only, and group 5 was the environmental control group. Each vaccination was carried out with 0.5 mL fish−1 vaccine and at 28 °C water temperature. Booster dose of respective vaccine was delivered on day 14, and all groups were challenged with 109 CFU mL−1 of live V. alginolyticus using intraperitoneal (IP) injection at 0.5 mL fish−1 on day 28. The relative percentage survival (RPS) was highest for rOmpK group at 100%, followed by rOmpW group at 63%, and E. coli BL21(DE3) group at 0%. The IgM antibody specific to V. alginolyticus was detected in the serum, in which both rOmpK and rOmpW vaccinated groups showed an increasing pattern in antibody level following vaccinations. The IgM against rOmpK showed significantly (p < 0.05) higher OD values than rOmpW at challenge on day 28 post vaccination. The results of this study suggest that rOmpK succeeded in providing excellent protection while the rOmpW succeeded in providing partial protection against infection by V. alginolyticus.